Competências coletivas no terceiro setor: estudo de caso em um projeto voluntário - Gamarra, Vilma Lorena Tello (Universidade do Vale do Rio dos Sinos, 2013)
Inside the competences approach that is focused in the human resources management, the collective competences perspective is an emergent research area. The collective competences are referred to the competences that are owned by a group of individuals; the same individuals that use the sensemaking process learn, interact and cooperate collectively, under a specific context, aiming to get a common activity. Different works have been addressed in this topic; however, more empirical and theoretical works are still necessary in order to help to the consolidation process of this area. The objective of this study is to understand the collective competences in a voluntary project of the third sector, in order to achieve this objective the dimensions of the collective competences have been identified, which are used in this work. The method employed was the study of a case, the object of study is the third sector, specifically a social project. Among the theoretical results obtained in this work were identified seven dimensions of the collective competences that are: collective knowledge, collective memory, compromising, shared understanding, sensemaking, action and coverage. Regarding to the empirical results referred to the understanding of the collective competences in the voluntary project of the third sector, we observed three results: (1) All the dimensions of the collective competences were proved in the project, furthermore, the dimensions of collective competences as collective knowledge, collective memory, action and coverage were easily identified for the project members; (2) those dimensions achieved to be determinant for the project performance, consequently, guarantee the project success, becoming the most representative project of all the projects managed for the NGO; (3) The seven dimensions influenced also the performance of all the NGO, this fact let to obtain new projects, with other international financial resources; (4) the dimensions of the collective competence of the project contributed to the social organizations practice the principles of transparency and accountability in their activities. Finally, the fact that confirms the collective competences dimensions as a key element of the development opens the possibility of advancing in the operationalization of this construct, where the next step would be a descriptive study.
Keywords: Collective; Dimensions; Competences; Third sector; Collective competences; DimensõesColetiva; Competências; Terceiro setor; Competências coletivas; ACCNPQ::Ciências Sociais Aplicadas::Administração